Effectiveness of Combined Tactical Forward Posts in Countering Enemy Drone Attacks - Nur Rachman Supadmana Muda; M. Faisal Fadilah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The rapid proliferation of small and low-cost unmanned aerial systems (UAS) has introduced complex threats, particularly swarm drone attacks that challenge conventional defense systems. Without an integrated command structure, defensive operations tend to be fragmented, resulting in poor situational awareness, delayed responses, and inefficient use of resources. This study examines the effectiveness of a Combined Tactical Forward Post (CTFP) as a centralized command and control node to enhance territorial defense against drone threats. The CTFP integrates multi-sensor inputs—including radar, radio frequency (RF) detection, electro-optical/infrared (EO/IR) systems, and unmanned platforms through sensor fusion and AI-assisted analysis to generate a real-time common operational picture. A layered defense model is proposed, consisting of detection, command and control, electronic warfare, kinetic engagement, and inner protection zones, enabling synchronized application of soft-kill and hard-kill measures. The results indicate that CTFP significantly improves detection accuracy, decision-making speed, and coordination across defensive units, particularly in handling swarm attacks through parallel tracking, threat prioritization, and adaptive response. Additionally, the incorporation of redundancy and distributed backup systems enhances operational resilience under contested conditions. Overall, the CTFP framework provides a comprehensive, adaptive, and scalable solution for countering modern drone threats, making it highly relevant for complex operational environments such as archipelagic regions.